2019
DOI: 10.1055/s-0039-1688734
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric Comparative Analysis between Oral Dysplastic Potentially Malignant Disorders and Oral Squamous Cell Carcinoma

Abstract: Objective This study aimed to determine the correlation between the vascular mast cells and inflammatory changes in the potentially malignant disorders, compared to the oral squamous cell carcinoma (OSCC) in varying degrees of dysplasia. Materials and Methods Thirty samples were selected: 10 of OSCC, 10 of oral leukoplakia, and 10 of actinic keratosis. The toluidine blue technique was used on the mast cells, and hematoxylin and eosin were used for analyzing the lymphocytes, mitosis, and vessels. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Furthermore, eosinophils infiltration was elevated in OSCC compared to dysplastic lesions suggesting that eosinophils may be necessary for malignant transformation (51). Similarly, both mast cells and eosinophil infiltration were increasingly elevated during the progression from normal epithelium to dysplasia to invasive cancer (52)(53)(54)(55). Currently, it remains unclear how other granulocytic cells alter the tumor microenvironment to facilitate the development pre neoplastic lesions and their transition to invasive cancer.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
“…Furthermore, eosinophils infiltration was elevated in OSCC compared to dysplastic lesions suggesting that eosinophils may be necessary for malignant transformation (51). Similarly, both mast cells and eosinophil infiltration were increasingly elevated during the progression from normal epithelium to dysplasia to invasive cancer (52)(53)(54)(55). Currently, it remains unclear how other granulocytic cells alter the tumor microenvironment to facilitate the development pre neoplastic lesions and their transition to invasive cancer.…”
Section: The Evolution Of the Immunosuppressive Microenvironment In Oplmentioning
confidence: 99%
“…The presence of atypical and degranulated mast cells was found in cases with the presence of moderate and intense inflammatory infiltrate. Pereira and Pinheiro [2019] ( 18 ), in a comparative study between potentially malignant lesions and oral squamous cell carcinoma, found that mast cell density was lower in oral leukoplakia when compared to lesions of (OSCC), which in turn presented a significant increase in mast cells and microvessels suggesting tumor progression and aggression through the positive regulation of angiogenesis by these cells. Sathyakumar et al [2012] ( 17 ), reported the highest concentration of mast cells and blood vessels in oral leukoplakia lesions when compared to the normal oral mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenesis facilitates the invasion and metastasis of cancer cells by remodeling the TME, and provides increased oxygen and nutrients for tumor growth. In the context of OSCC, a positive correlation between the MC and vascular densities in OSCC has been recently established, suggesting the ability of these cells to regulate angiogenesis [ 107 ]. This may explain the aggressive behavior and metastatic tendencies of these oral tumors.…”
Section: Oscc Immune Permissive Environment Induced By Periodontal Diseasementioning
confidence: 99%